A Critical Review on the Comparative Assessment of Rare-Earth and Non-Rare-Earth Alloying in Magnesium Alloys - Hafiz Muhammad Rehan Tariq; Muhammad Ishtiaq; Hyun-Hak Kang; Umer Masood Chaudry; Tea-Sung Jun (Metals)
Magnesium (Mg) alloys have emerged as highly sought-after alloys in aerospace, automotive, and biomedical engineering industries due to their low density and excellent mechanical properties. The addition of alloying elements plays a critical role in improving the performance of these Mg alloys, with rare-earth (RE) elements being especially helpful in improving mechanical properties, specifically strength and ductility. However, due to the higher cost and limited availability of RE elements, researchers are trying to explore non-rare-earth (non-RE) alternatives, such as aluminum, calcium, zinc, etc. These non-RE elements offer various advantages including cost effectiveness and enhanced manufacturability, but they may not always match the performance improvements of RE elements. This review critically examines and compares the effects of RE and non-RE alloying elements on the microstructural evolution, corrosion resistance, and strengthening implications of Mg alloys. Furthermore, it explores the recent advancements in alloy development and evaluates the trade-offs between RE and non-RE alloying elements, offering key insights into the optimal approaches for enhancing the performance of Mg alloys across various applications.